2022
DOI: 10.3390/biomedicines10092259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity of the Combinational Treatment of Noozone Cold Plasma with p-FAK Antibody-Conjugated Gold Nanoparticles in OSCC Xenograft Mice

Abstract: Oral squamous cell cancer (OSCC) is the most common type of oral cancer (about 80–90% of cases) and various research is being done to cure the disease. This paper aims to verify whether treatment with no-ozone cold plasma (NCP), which is designed for safe usage of the plasma on oral cavities, in combination with gold nanoparticles conjugated with p-FAK antibody (p-FAK/GNP) can trigger the selective and instant killing of SCC-25 cells both in vitro and in vivo. When SCC25 and HaCaT cells are exposed to p-FAK/GN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Other polymeric nanoparticles based on natural or synthetic biopolymers are conjugated with mAb and are carriers of anticancer drugs, such as as doxorubicin (DOX), paclitaxel (PTX), epirubicine, and cisplatin [ 17 , 18 , 19 , 20 , 21 ]. Many other nanocarriers have been conjugated with mAb, e.g., dendrimers [ 22 ], gold nanoparticles [ 23 ], and magnetic nanoparticles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other polymeric nanoparticles based on natural or synthetic biopolymers are conjugated with mAb and are carriers of anticancer drugs, such as as doxorubicin (DOX), paclitaxel (PTX), epirubicine, and cisplatin [ 17 , 18 , 19 , 20 , 21 ]. Many other nanocarriers have been conjugated with mAb, e.g., dendrimers [ 22 ], gold nanoparticles [ 23 ], and magnetic nanoparticles [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this study was conducted in an in vitro system only, the results suggested that CAP could have considerable treatment benefits, considering that surgery is the only treatment option for chondrosarcoma. The research article by Choi et al suggested novel approaches for using CAP in combination with gold nanoparticles to treat oral squamous cell carcinoma (OSCC) [ 4 ]. According to the research therein, they applied a no-ozone cold plasm to SCC25 and HaCaT cell lines in combination with gold nanoparticles conjugated with the antibody-targeting p-FAK protein (p-FAK/GNP); this combinational treatment successfully triggered OSCC-specific immediate cell death.…”
Section: Articles Introducing the Anticancer Effect Of Direct Treatme...mentioning
confidence: 99%